Physical therapy case files acute care - Jobst, Erin E (McGraw-Hill Medical, 2013)
Realistic acute care cases help physical therapy students make the transition from classroom to clinic. Physical Therapy Case Files: Acute Care delivers 35 acute-care cases that help students sharpen their critical thinking skills and prepare them for real-world practice. Clinicians will find the book to be a valuable refresher. Each case includes clinical tips, evidence-based practice recommendations, analysis, and references. Features National Physical Therapy Examination-style review questions accompany each case to prepare students for the boards. Provides students with practical experience before working with patients. Spares instructors from having to create their own cases. Analysis of case includes remediation content, saving students the necessity of having to go a textbook for answers.